Manhood enslaved : bondmen in eighteenth- and early nineteenth-century New Jersey - Marshall, Kenneth E. (Kenneth Edward) (Gender and race in American history, 2011)
Manhood Enslaved reconstructs the lives of three male captives to bring greater intellectual and historical clarity to the muted lives of enslaved peoples in eighteenth- and early nineteenth-century central New Jersey, where blacks were held in bondage for nearly two centuries. The book contributes to an evolving body of historical scholarship arguing that the lives of bond people in America were shaped not only by the powerful forces of racial oppression, but also by their own notions of gender. The book uses previously understudied, white-authored, nineteenth-century literature about central New Jersey slaves as a point of departure. Reading beyond the racist assumptions of the authors, it contends that the precarious day-to-day existence of the three protagonists -- Yombo Melick, Dick Melick, and Quamino Buccau (Smock) -- provides revealing evidence about the various elements of "slave manhood" that gave real meaning to their oppressed lives. Kenneth E. Marshall is Assistant Professor of History at the State University of New York at Oswego.